Asymmetries of foot strike patterns during running in high-level female and male soccer players - Siegel, S. D.; Mason, J.; Hamacher, D.; Rahlf, A. L.; Zech, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Backround Foot strike pattern (FSP) is defined by the way the foot makes initial ground contact and is influenced by intrinsic and extrinsic factors. This study investigated the effect of running speed on asymmetries of FSP.